Το 1922 και η προσφυγιά στην ελληνική και την τουρκική αφήγηση - Demirozu, Damla (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2011)
The representation of the same historical fact might embody differences between different societies and sometimes even in the same society. The 1922 refugees and the Exchange of Population is one of those events which are marked and associated differently in Greek and Turkish collective memories and societies. This article aims to analyse associations of 1922 in Greek and Turkish narratives.